Pengembangan Sistem Pengelolaan Surat Perusahaan Menggunakan Metode Agile Pada PT. Indo Mutiara Global - Deanova, Ryanda; Fatmah, Adinda; Shafa Apta Hermawan, Lu’ay; Saprudin (CV. Shofanah Media Berkah, 2024)
Efficient document management is a critical component in supporting smooth operations and decision-making within companies. PT. Indo Mutiara Global faces challenges with manual document handling, leading to delays, recording errors, and difficulties in document retrieval. This study aims to develop an Agile-based document management system that is adaptive and responsive to the changing needs of the company. Using the Agile method, the system is developed incrementally, allowing continuous improvement based on user feedback. The system's implementation is expected to accelerate administrative processes, reduce errors, and improve document management efficiency at PT. Indo Mutiara Global. The research findings show that the Agile-based document management system enhances accuracy and speeds up document retrieval, positively impacting the company's productivity and efficiency.